Pengelolaan Villa Sanyas Dalam Mengatasi Ketidaknyamanan Wisatawan Terhadap Aktivitas Wisata Malam Di Kawasan Seminyak Bali - Tibuludji, Pinkqi Gracesyani; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i01.p05, 2018)
The research is located in Villa Sanyas area of Seminyak-Kuta Bali. The research was conducted to find out how the management villa sanyas, and also to know the factors that make the tourist stay at villa sanyas feel uncomfortable. the choice of Seminyak as the location of this research according to th place where the tourism grows fastly. On the development stage, that tourism area still need various research from some point of view. Thus, this research focuses to identify factors which affects the uncomfortness during stay in Villa Sanyas Seminyak. This research is very important and could be reference as solutions for comfortness of tourists in Villa Sanyas. The method of data collecting in this research are observation, interview, and documentation to analyze the data collected  with descriptive qualitative analysis while primary data and secondary data. The determining of informants use is purposive sampling. Results of the study found that most tourist who stay at villa sanyas feel disturbed by the noise can be heard up to the villa, besides that also some employees who work in villa sanyas not fluent in english. Based on the report, can be suggested to the villa management to improve the quality of service toward the tourists who stay, then the tourist will feel comfort. Keywords : comfortness, tourists, management and night tourism .